2013
DOI: 10.1007/s10637-013-9932-0
|View full text |Cite
|
Sign up to set email alerts
|

Polycationic calixarene PTX013, a potent cytotoxic agent against tumors and drug resistant cancer

Abstract: Summary Previously, we reported on the anti-tumor activities of two designed calix[4]arene-based topomimetics (PTX008 and PTX009) of the amphipathic, angiostatic peptide Anginex. Here, we chemically modified the hydrophobic and hydrophilic faces of PTX008 and PTX009, and discovered new calixarene compounds that are more potent, cytotoxic anti-tumor agents. One of them, PTX013, is particularly effective at inhibiting the growth of several human cancer cell lines, as well as drug resistant cancer cells. Mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…[116] The peptidomimetics were also further modified and their in vitro and in vivo efficacy was further improved showing over 100-fold higher effect in vitro than the original topomimetics against certain endothelial cells such as SCK and A549. [125] However, the compounds showed dose-dependent toxicity in mice at high doses which had not been reported for an anginex-based therapy before. [125] Overall, anginex and its mimetics are very potent antiangiogenics that have the ability to localise to angiogenically activated endothelial cells and display cytotoxicity to these cells, resulting in decreased vascularisation and decreased tumour growth.…”
Section: Peptide-based Inhibitorsmentioning
confidence: 84%
See 1 more Smart Citation
“…[116] The peptidomimetics were also further modified and their in vitro and in vivo efficacy was further improved showing over 100-fold higher effect in vitro than the original topomimetics against certain endothelial cells such as SCK and A549. [125] However, the compounds showed dose-dependent toxicity in mice at high doses which had not been reported for an anginex-based therapy before. [125] Overall, anginex and its mimetics are very potent antiangiogenics that have the ability to localise to angiogenically activated endothelial cells and display cytotoxicity to these cells, resulting in decreased vascularisation and decreased tumour growth.…”
Section: Peptide-based Inhibitorsmentioning
confidence: 84%
“…[125] However, the compounds showed dose-dependent toxicity in mice at high doses which had not been reported for an anginex-based therapy before. [125] Overall, anginex and its mimetics are very potent antiangiogenics that have the ability to localise to angiogenically activated endothelial cells and display cytotoxicity to these cells, resulting in decreased vascularisation and decreased tumour growth. The role of galectin-anginex interactions in the anti-angiogenic effect is debatable and further studies are necessary to confirm whether the compounds are truly inhibitors or activators of galectins.…”
Section: Peptide-based Inhibitorsmentioning
confidence: 84%
“…Cancer progression has been suggested to include the loss of cell cycle checkpoint controls that regulate passage through the cell cycle (Pelizzarorocha et al, 2013;Ji et al, 2017). According to the literatures, Dings and co-workers (Dings et al, 2013) have revealed that calixarene amine derivative PTX013 had good cytotoxicity to cancer cells and blockades the cell cycle of SQ20B at G0/G1 phase. In addition, Pelizzarorocha et al (2013) found that tert-butyl calix[6]arenes can cause cell cycle arrest in G0/G1 phase by down-regulating key proteins, such as PIM1, CDK2, and CDK4.…”
Section: Flow Cytometry For Mcf-7 Cell Cycle and Apoptosis Analysismentioning
confidence: 99%
“…Ongoing clinical trials aim to reveal the therapeutic benefit of targeting galectin‐1 in cancer patients . In addition, continuing efforts are undertaken to develop novel galectin‐1‐targeting molecules for diagnostic and therapeutic purposes . In this article, we used a rational approach to generate antibodies with pre‐defined epitope specificity and selectivity for galectin‐1.…”
Section: Introductionmentioning
confidence: 99%
“…11 In addition, continuing efforts are undertaken to develop novel galectin-1-targeting molecules for diagnostic and therapeutic purposes. 24,25 In this article, we used a rational approach to generate antibodies with pre-defined epitope specificity and selectivity for galectin-1. We demonstrate that with this approach we were able to generate antibodies that are specific for galectin-1 and reactive in multiple species, making them excellent candidates for tissue analysis in experimental and clinical setups.…”
Section: Introductionmentioning
confidence: 99%